Kualitas Pelayanan, Fasilitas Fisik, Dan Peromosi Terhadap Kepuasan Konsumen Pada Hotel Aneka Lovina Villas & Spa - Ni Luh Nurkariani; Komang Yushi Hermawati (ARTHA SATYA DHARMA, 2021)
The purpose of this study was to determine the effect of service quality, physical facilities and promotions on consumer satisfaction at Aneka Lovina Villas & Spa Hotel. This research was conducted at Aneka Lovina Villas & Spa hotel with the observed population were all visitors of Aneka Lovina hotel. As many as 94 people were drawn from guests or visitors who have used Aneka Lovina Hotel services randomly (random sampling technique). Data collected by giving questionnaires to the sample. The data obtained were analyzed by multiple linear regression with the help of IBM SPSS 25.Based on the results of data analysis obtained the relationship between independent and dependent variables as follows Y = 2.804 + 0.244 X1 + 0.406 X2 + 0.080 X3. Partially, service quality influences customer satisfaction with a t value of 10,193, physical facilities affect customer satisfaction with a t value of 5,561, and promotion influences customer satisfaction with a t value of 2,369. Simultaneously variable service quality, physical facilities and promotions significantly influence customer satisfaction with an F value of 175,830.